Soul, God, Sin and Afterlife in Dialect Discourse of Volga-Dvina Interfluve - E. S. Kogan (Научный диалог, 2017)
The article is devoted to the study of the ideas about spiritual religious categories shown in the discourse of dialect speakers in the territory of the Volga-Dvina Interfluve (Arkhangelsk, Vologda, Kostroma regions). Ways of describing such concepts as “soul,” “God,” “sin,” “conceptions of the afterlife” in the stories of informants are covered. The analysis of contextual compatibility, words-partners, in some cases - metaphorical meanings is presented. Models of perception and description of spiritual concepts in the national discourse are offered. Also, for comparison we use the results of studies of the spiritual realm through the prism of folklore and ancient Russian literary tradition. People’s perception of religious categories is compared with the position of the official Church tradition. The research urgency is caused by appeal to speech material showing a picture of the world that is relevant to the consciousness at the present time, not archaic, enshrined in the language. Also the relevance of the work is caused by the fact that a new material is introduced - data of field records of the Toponymic expedition of the Ural Federal University. The hypothesis is presented about the perception by people’s consciousness of the soul as a kind of “double” of a person in the field of both physical and emotional; God as the generalized concept of the spiritual realm in general; sin as a material object; underworld as the official administrative structure.